Carboxyhemoglobin levels in children during extracorporeal membrane oxygenation support: a retrospective study. (November 2022) - Kimura, Satoshi; Gelbart, Ben; Chiletti, Roberto; Stephens, David; Butt, Warwick
Introduction: Hemolysis is a common complication of extracorporeal membrane oxygenation (ECMO). There are few data on whether carboxyhemoglobin (COHb), a potential marker of hemolysis, are elevated during ECMO support. Methods: We conducted a single-center, retrospective study comparing peak COHb levels of children pre-, during, and post-ECMO from January 2017 to August 2020. Results: There were 154 ECMO runs in 147 children (154 PICU admissions) included in the study. The median age was 3.5 (IQR 0.2, 39.2) months. Veno-arterial ECMO was the predominant mode: 146/154 (94.8%). Eighty-seven children (56.5%) underwent cardiac surgery. Peak COHb levels during ECMO were statistically significantly higher compared to pre ECMO (COHb 1.8% (IQR 1.4, 2.6) vs COHb 1.2% (IQR 0.7, 1.7), p < 0.001) and post ECMO (COHb 1.6% (IQR 1.3, 2.2), p = 0.009). Children with COHb ⩾2% were younger and had longer duration of ECMO support. Plasma hemoglobin weakly correlated with COHb level ( r = 0.14; p = 0.04). Conclusions: Carboxyhemoglobin levels increased during ECMO support compared to the pre and post ECMO period. Younger age and longer ECMO duration were associated with COHb levels ⩾2%. Plasma hemoglobin weakly correlated with COHb level.